2021
DOI: 10.5194/se-12-1515-2021
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Iberian Massif as deduced from its crustal thickness and geometry of a mid-crustal (Conrad) discontinuity

Abstract: Abstract. Normal incidence seismic data provide the best images of the crust and lithosphere. When properly designed and continuous, these sections greatly contribute to understanding the geometry of orogens and, along with surface geology, unraveling their evolution. In this paper we present the most complete transect, to date, of the Iberian Massif, the westernmost exposure of the European Variscides. Despite the heterogeneity of the dataset, acquired during the last 30 years, the images resulting from repro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 115 publications
(203 reference statements)
0
10
0
1
Order By: Relevance
“…The sinking of part of the upper will then explain why the Tagus Basin has lower topography than the Duero Basin. Ayarza et al (2021a) have interpreted the mid-crustal discontinuity identified throughout the Iberian Massif as the rheological boundary between the upper and lower crust pointing that its geometry, position and extent are consistent with the characteristics of the Conrad discontinuity.…”
Section: Controlled Source Seismic Profilingmentioning
confidence: 77%
See 1 more Smart Citation
“…The sinking of part of the upper will then explain why the Tagus Basin has lower topography than the Duero Basin. Ayarza et al (2021a) have interpreted the mid-crustal discontinuity identified throughout the Iberian Massif as the rheological boundary between the upper and lower crust pointing that its geometry, position and extent are consistent with the characteristics of the Conrad discontinuity.…”
Section: Controlled Source Seismic Profilingmentioning
confidence: 77%
“…The Moho appears as a near horizontal discontinuity at approximately 30-33 km depth. The compressional tectonics in the Central Iberian System, has been imaged using a dense wide-angle seismic reflection data profile (Ayarza et al, 2021a), global phase interferometry (Andrés et al, 2019) and ambient seismic noise (Andrés et al, 2020). These data constrain a normal velocity model with velocities of 6.0-6.2 km/s, increasing to 7.0 km/s in the lower crust and a limited root under the core of the Central Iberian system reaching locally a depth of 38 km.…”
Section: Controlled Source Seismic Profilingmentioning
confidence: 99%
“…This pattern is not observed in other ranges formed in the borders of the Iberian microplate, that is, the Cantabrian Mountains, where Teixell et al (2018) proposed the preservation of the mid-crustal detachment allowed for underthrusting of the lower crust. Accordingly, we suggest that the crustal structure and deformation mechanisms affecting Gredos during the Alpine contraction are significantly controlled by the inferred volume of granitoids at depth, playing a role in the nucleation of the SPCS (de Vicente et al, 2018), and enhancing coupled Alpine deformation between the upper and lower crust (Ayarza et al, 2021).…”
Section: The Conrad Discontinuity: the Upper-lower Crust Boundarymentioning
confidence: 79%
“…The structure of the SPCS has attracted significant attention mainly due to its high topography in the interior of a tectonic plate. So far, research efforts have focused on finding models to explain the observed intraplate deformation (Cloetingh et al, 2002;De Vicente et al, 1996;de Vicente & Vegas, 2009;Vegas & Suriñach, 1987), the different tectonic and stratigraphic evolution of its foreland basins (de Vicente & Muñoz-Martín, 2013;Fernández-Lozano et al, 2011;Silva et al, 2017), its lithospheric structure (Andrés et al, 2019(Andrés et al, , 2020Ayarza et al, 2021), and the tectonic origin of its topography (Casas-Sainz & de Vicente, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation